2015
DOI: 10.1016/j.cell.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Restriction on Pluripotent State Dissolution by Cell-Cycle Pathways

Abstract: During differentiation, human embryonic stem cells (hESCs) shut down the regulatory network conferring pluripotency in a process we designated pluripotent state dissolution (PSD). In a high-throughput RNAi screen using an inclusive set of differentiation conditions, we identify centrally important and context-dependent processes regulating PSD in hESCs, including histone acetylation, chromatin remodeling, RNA splicing, and signaling pathways. Strikingly, we detected a strong and specific enrichment of cell-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
211
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(234 citation statements)
references
References 49 publications
23
211
0
Order By: Relevance
“…A recent study has revealed another interesting connection between exit from pluripotency and early cell fate decisions, this time involving S phase and G2 phase. In this study, a high-throughput RNA interference (RNAi) screen performed in human embryonic stem cells (hESCs) identified cell cycle genes involved in DNA replication and G2-phase progression that restrict exit from pluripotency or 'pluripotent state dissolution' (Gonzales et al, 2015). This is another line of evidence that supports the idea that the cell cycle state of PSCs is related to maintenance of pluripotency.…”
Section: Entry To and Exit From G1 Phasesupporting
confidence: 52%
“…A recent study has revealed another interesting connection between exit from pluripotency and early cell fate decisions, this time involving S phase and G2 phase. In this study, a high-throughput RNA interference (RNAi) screen performed in human embryonic stem cells (hESCs) identified cell cycle genes involved in DNA replication and G2-phase progression that restrict exit from pluripotency or 'pluripotent state dissolution' (Gonzales et al, 2015). This is another line of evidence that supports the idea that the cell cycle state of PSCs is related to maintenance of pluripotency.…”
Section: Entry To and Exit From G1 Phasesupporting
confidence: 52%
“…In accordance with our indings in PA1 cells after ETO treatment, a recent high-throughput RNAi screen revealed the intrinsic roles of S and G2, functionally establishing that pluripotency control is hardwired to the cell-cycle machinery and that the ATM/ATR-CHEK2-p53 axis enhances the TGF-b pathway to prevent premature cell death [36]. As well, [3] showed that cellular senescence accompanying DNA damage or DNA damage as such favors cell reprogramming in vivo models.…”
Section: Ovarian Germline Cells Challenged By Genotoxic Stress Displasupporting
confidence: 48%
“…Therefore, damaged ESC cells typically accumulate in the G2 DNA damage checkpoint instead, whose relative weakness allows mitotic slippage [35,36]. Moreover, stressed ESC and likely also CSC possess a peculiar intermediate post-slippage phase (not 4 N-G1) [37,38] containing non-degraded cyclin B1, which is normally destroyed after mitosis.…”
Section: Biological Features Of Cell Senescence: What Is Clear and Whmentioning
confidence: 99%
“…In Drosophila female GSCs, the G1 phase is also short and most of the cell cycle is spent in G2 (18). In addition, recent work in human embryonic stem cells shows that the maintenance of their pluripotency is actively controlled in S and G2 phases, through the ATM and Cyclin B1 pathways (20). Because Drosophila GSCs exhibit an extended G2 phase, their self-renewal ability could similarly be maintained during this phase.…”
mentioning
confidence: 95%